2010
DOI: 10.1287/opre.1090.0760
|View full text |Cite
|
Sign up to set email alerts
|

Gradient Estimation for Multicomponent Maintenance Systems with Age-Replacement Policy

Abstract: We consider multicomponent maintenance systems with an F -failure group age-replacement policy: it keeps failed components idling until F components are failed and then replaces all failed components together with the nonfailed components whose age has passed the critical threshold age n for components of type n. With each maintenance action, costs are associated. We derive various unbiased gradient estimators based on the measure-valued differentiation approach for the gradient of the average cost. Each estim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
10
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 41 publications
0
10
0
Order By: Relevance
“…Some recent and classical survey articles on maintenance optimization can be found be Refs. [7,33,34] Other noteworthy recent contributions are: Dayanik and Gurler, [11] Dogramaci and Fraiman, [12] Heidergott and Farenhorst-Yuan, [15] Kurt and Kharoufeh, [23] Makis and Jiang, [27] and Ulukus et al, [32] among others. In addition to the theoretical work done in this area, maintenance models have been successfully applied in many real world applications including furnace erosion prediction using the state-space model, [8] transmission fault detection using the proportional hazards model, [26] and helicopter gearbox state assessment using the hidden Markov model.…”
Section: Introductionmentioning
confidence: 99%
“…Some recent and classical survey articles on maintenance optimization can be found be Refs. [7,33,34] Other noteworthy recent contributions are: Dayanik and Gurler, [11] Dogramaci and Fraiman, [12] Heidergott and Farenhorst-Yuan, [15] Kurt and Kharoufeh, [23] Makis and Jiang, [27] and Ulukus et al, [32] among others. In addition to the theoretical work done in this area, maintenance models have been successfully applied in many real world applications including furnace erosion prediction using the state-space model, [8] transmission fault detection using the proportional hazards model, [26] and helicopter gearbox state assessment using the hidden Markov model.…”
Section: Introductionmentioning
confidence: 99%
“…Alternatively, a variant of the score function method, called the push-out score function, has been developed for this kind of threshold optimization in inventory models; see [35], as well as [36] for an early reference. For a perturbation analysis of a maintenance model where θ triggers (preventive) maintenance of system components whose age exceeds θ , we refer to [19,16]. Finally, for applications to financial models, where θ is the value of a barrier in some option model, we refer to [15,31,17,21].…”
Section: Introductionmentioning
confidence: 99%
“…Maintenance of physical equipment, machinery, systems and even complete infrastructure represents an essential process for ensuring successful operation. It helps minimizing downtime of technical equipment [1], eliminate the risk thereof [2], or prolong the life of systems [3]. Maintenance is often enforced by external factors, such as regulations or quality management [4].…”
Section: Introductionmentioning
confidence: 99%
“…For instance, the International Air Transport Association (IATA) reported that maintenance costs of 49 major airlines increased by over 3 percent from 2012 to 2016, finally totaling $15.57 billion annually. 1 Decision support in maintenance can be loosely categorized according to two different objectives depending on whether they serve a corrective or preemptive purpose. 2 The former takes place after the failure of machinery with the goal of restoring its operations back to normal.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation